Pelatihan Peningkatan Kapasitas Sumber Daya Manusia Dalam Negosiasi Binsis UMKM di Lingkungan Provinsi Papua Selatan - Adi Maulana Rachman; Okto Irianto; Elly Noer (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2025)
Increasing human resource capacity in business negotiations is one of the strategic efforts to empower the Papuan people. This article is the result of implementing business negotiation training designed by the South Papua Provincial Government, Small and Medium Enterprises Cooperatives, Industry and Trade Service for involving academics from Musamus University the indigenous Papuan community in South Papua Province. The aim of the activity is to improve business negotiation skills to support the sustainability of small and medium enterprises (SMEs) managed by local communities. Training methods include participatory approaches, simulations, and case studies on business negotiations. The results of the training showed an increase in participants' understanding of effective negotiation techniques, business planning, and strategies for dealing with market dynamics.